2022
DOI: 10.1021/acsestwater.2c00017
|View full text |Cite
|
Sign up to set email alerts
|

Robust Adsorption and Persulfate-Based Degradation of Doxycycline by Oxygen Vacancy-Rich Copper-Iron Oxides Prepared through a Mechanochemical Route

Abstract: Persulfate-based advanced oxidation over heterogeneous catalysts is an effective approach to degrade organic pollutants, and prior adsorption of the pollutants on the catalysts is an essential step. In this study, CuO/Fe 2 O 3 (CF) composite materials with a robust adsorption capacity and catalytic activity toward organic pollutants were prepared using a green mechanochemical route. The raw CuO and α-Fe 2 O 3 present in the materials were transformed into CuFe oxide catalysts with abundant oxygen vacancies dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 67 publications
(93 reference statements)
0
6
0
Order By: Relevance
“…18,19 Furthermore, it can expose the internal parts of the materials and produce larger surface areas and more accessible catalytically active sites in them. 20 In one of our previous studies, for example, we showed that Co−Mn−W mixed oxides synthesized by ball milling could generate reactive oxygen species from persulfate to degrade doxycycline in wastewater. 21 In another study, CuO and Fe 2 O 3 composite materials synthesized using ball milling were shown to remove doxycycline via adsorption and persulfate activation.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…18,19 Furthermore, it can expose the internal parts of the materials and produce larger surface areas and more accessible catalytically active sites in them. 20 In one of our previous studies, for example, we showed that Co−Mn−W mixed oxides synthesized by ball milling could generate reactive oxygen species from persulfate to degrade doxycycline in wastewater. 21 In another study, CuO and Fe 2 O 3 composite materials synthesized using ball milling were shown to remove doxycycline via adsorption and persulfate activation.…”
Section: Introductionmentioning
confidence: 94%
“…21 In another study, CuO and Fe 2 O 3 composite materials synthesized using ball milling were shown to remove doxycycline via adsorption and persulfate activation. 20 MnO 2 synthesized by ball milling was also demonstrated to remove tetrabromobisphenol A in solutions better than MnO 2 produced by conventional methods. 13 Based on these previous reports, we hypothesized that ball milling could increase the oxygen vacancy on La 2 O 3 and thereby improve its photocatalytic activity to degrade emerging pollutants.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Fresh leaves (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) from a healthy guava tree were taken and washed thoroughly with DI water. These leaves were cut into small pieces and put into a beaker containing 300 mL DI water.…”
Section: Preparation Of Guava Leaf Extractmentioning
confidence: 99%
“…CuO/Fe 2 O 3 nanocomposite have been synthesized by a few research groups and explored for various applications like oxidation of n-hexane, oxidation of carbon monoxide, degradation of organic pollutants [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%